International policies for sustainable development from cultural empowerment. Issue 2 (15th May 2017) - Froner, Yacy-Ara
Abstract : Purpose: The purpose of this paper is to explore the international agenda regarding the discussion on the sustainable development. It asserts the idea that economic growth is a process that embraces the cultural values, human capability, and transnational policies aimed to guide and support the efforts of nations to achieve social security. The paper places the issues of contemporary heritage science theory on the recent debate concerning the cultural heritage preservation based on scientific, legal, social, and management issues. Design/methodology/approach: The paper selected mainly reports, declarations, resolutions, and recommendations concerning this theme. The framework comprehends almost 30 years: from the first project titled "World Decade of Cultural Development" (1988) to the last conference in Tanzania (2016). Some questions defined the methodological approach of this investigation: how can we generate sustainability in terms of the use, maintenance, and conservation of cultural heritage? How can we adjust the local, national, and international guidelines to a common logic without letting go of the community autonomy? Findings: The paper provides a historical context about the enlargement of the debate concerning the international policies for sustainable development from cultural empowerment. It suggests that UNESCO, WHC, and ICCROM have been promoting positive projects in vulnerable regions. Research limitations/implications: Eurocentric models of development and occidental concept of culture exposure in the selected documents should be reviewed mainly in decolonization areas. Practical implications: The article offers a distinct perspective for the system of international evaluation of cultural heritage, and a different focus of reflection for the academic community. Originality/value: The study promotes a reflection regarding the international agenda for sustainable development over the last 30 years.